Adaptation strategies followed by the livestock rearers of Coastal Odisha and West Bengal to cope up with climate change - MAITI, SANJIT; JHA, SUJEET KUMAR; GARAI, SANCHITA; NAG, ARINDAM; CHAKRAVARTY, R; KADIAN, K S; CHANDEL, B S; DATTA, K K; UPADHYAY, R C (The Indian Journal of Animal Sciences, 2014)
Adaptation to climate change and variability has recently become a subject of increasing importance in climate change research with an objective to reduce the vulnerability of climate sensitive people. The present study was designed to identify and assess the adaptation strategies followed by the climate sensitive livestock rearers of coastal Odisha and West Bengal. Livestock rearers (480) were selected from 4 coastal districts of Odisha and West Bengal. The study revealed that 17 adaptation strategies were followed by the livestock rearer. To trace the relative importance among the adaptation strategies, an exclusively climate change adaptation index was developed. It was observed that change in micro-climate in cattle shed/grazing area/stall was the most preferred adaptation strategy followed by providing the frequent clean and fresh drinking water and additional washing/sprinkling of cattle and buffaloes. Livestocks are very much susceptible to heat stress. Therefore, most of the livestock rearers followed heat alleviating adaptation strategies.